PENGAWASAN PERIZINAN DEPOT AIR MINUM DI KELURAHAN SIMPANGBARU KECAMATAN TAMPAN - Chandra, Pivit Septiary; Harahap, Tuti Khairani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
From the data obtained from the Department of Health (Dinas Kesehatan)(attachments 2, in 2012 was recorded 25 depots drinking water and 10 depotswhich inspected and only 8 depots are eligible. Of such data seen that from yearto-year increasing the amount of drinking water depots but that only has licensefrom the Department of Health has decreased. Only 25% percent of the amountdrinking water depots listed on the Department of Health which inspected andeligible. The method in this research is descriptive of qualitative the researchmethod, which describe or explain the problem the existing with the providinganswers to issues raised. This research focuses on the problems that existed atwhen the research is conducted (at the moment) or the problem that are actual.Hence solving problems the existing done by way of describing a situation, thedata, the status of phenomena based on the facts the existing.Based on the result of research and analysis conducted and researchershave described in the previous chapter, regarding supervision of drinking waterdepots license in Kelurahan Simpangbaru Tampan, then can be concluded fromindicator that researchers use for the view how to surveillance drinking waterdepots license in Kelurahan Simpangbaru Kecamatan Tampan, which sets thestandard, factor system of surveillance, surveillance conducted quite well, provedwith already the drinking water depots supervised conduct production activities inaccordance with the standards given. This is accomplished with the advancesocialization and coaching. However which can be seen also that the there aresome areas which have not conducted such as surveillance KelurahanSimpangbaru. So that depots which not authorized in that area growing. Thequality factor of surveillance conducted Disperindag has not well done because isstill find many constraints such as coordination has not been created with the boththe Department of Health as well as the limited time, funds, and facilities inconducting surveillance.Keyword: license, surveillance, depot of drinking water.